A therapeutic group for young people with diverse gender identifications. (April 2019) - Davidson, Sarah; Morrison, Annabelle; Skagerberg, Elin; Russell, Ian; Hames, Anna
Young people are presenting to specialist gender services in higher numbers than before and many with significant psychosocial difficulties. Negative experiences of stigma, difficult peer relationships and discrimination exacerbate distress and psychological difficulties, negatively impacting wellbeing and resilience. Social support is advocated as a means of supporting young people with diverse gender identifications, such as through peer support groups. This article describes the establishment of a young persons' group in 2011 within the United Kingdom's Gender Identity Development Service (GIDS), for those attending the service as a means of enabling their coping with difficult experiences and facilitating their wellbeing and resilience through effective social support. The group was evaluated using qualitative and quantitative measures and has subsequently run each year. Now in its sixth year, the authors reflect on their learning and experiences.